Development and evaluation of ergonomics and psycosocial assessment method for assessing work-related upper limb disorders - Abd Razak, Noor Syafiqa (2018)
The observational methods have been considered as the most widely used for assessing work-related upper limb disorders (WULDs) because it is inexpensive, practical to use, and flexible to use in a wide range of workplaces. However, the existing methods have a specific purposes and do not universally ideal for all risk factors. Most of the existing methods only focus on assessing physical risk factors of WULDs especially in body postures and do not considered other factors of WULDs such as psychosocial, work organizational, and individual risk factors. Nowadays, psychosocial work characteristics are recognized as important risk factors. Besides that, during the tool development process, it was found that some of the existing observational methods have limited work perform the reliability, usability, and validity analysis. In order to improve these limitations, this study aims to develop a new observational method known as Upper Limb Risk Assessment (UPLIRA) tool and to determine the reliability and validity of the UPLIRA tool. The initial development of UPLIRA tool was conducted in three stages including the development of the UPLIRA system components, development of the UPLIRA checklist (prototype), and psychometric properties evaluation (reliability and validity). In reliability trials, the results of inter and intra rater reliability shows good (K = 0.802 - 0.806) to very good (K = 0.811 - 0.833) agreement among the observers. Meanwhile, the usability trials shows that the UPLIRA tool was applicable to wide range of jobs/tasks, valuable at works, and action level is easy to understand (mean 4.17 ± 0.753). Whereas, in validity trials the highest risk scores were obtained by cashier workers contrast to office workers according to the UPLIRA assessment. Based on the results so far, it can be concluded that the UPLIRA tool was found to be practically reliable and applicable to a wide range of workplaces.